Between Medina del Campo and Rome: A journey of money in the sixteenth century - Isabella Iannuzzi (The Journal of European Economic History (JEEH), 2022)
During the early modern age, shaping the mechanisms and guarantees of financial and commercial transactions was the basis for the expansion of commercial markets: the beginning of market globalization was due not only to the discovery of a new continent and new trade routes, but also to the manner of being in contact with these new territories and of including them economically and financially in a perspective of political development. The credit instruments were an important tool and the Catholic monarchy was at the forefront of the use of the most appropriate instruments to implement a system of control and domination at a political and financial-economic level.1 This article investigates an episode - the refusal of the Colegio de Santa María de los Ángeles de la Universidad de Salamanca to pay the difference between old and new chamber ducats, generated in a payment made in Rome; this is a clear example of the complexities of the financial transactions made in Rome that were the result of benefits, concessions and graces of various kinds. The network of relations involved in the quarrel proves the ability of Antonio de Fonseca, a Portuguese banker living in Rome, who was to become an important financial asset in the Italian and curial environment for the Castillan banker Simón Ruiz. Viceversa, Simon Ruiz, too was an excellent contact for Fonseca who used him to find out what was happening within the Catholic monarchy at a time as delicate as its union with the Portuguese king- dom (1580-1640). Their correspondence depicts the dynamics and complexities of the contacts between "hombres de negocios" through the Iberian Peninsula and Rome.
Keywords: 330; Credit market; International financial market; Rome; Portugal; Spain; Kreditmarkt; Internationaler Finanzmarkt; Rom; Portugal; Spanien